Comparative Study of 5-Day and 10-Day Cefditoren Pivoxil Treatments for Recurrent Group A β-Hemolytic Streptococcus pharyngitis in Children - Hideaki Kikuta; Mutsuo Shibata; Shuji Nakata; Tatsuru Yamanaka; Hiroshi Sakata; Kouji Akizawa; Kunihiko Kobayashi (International Journal of Pediatrics)
Efficacy of short-course therapy with cephalosporins for treatment of group A β-hemolytic streptococcus (GABHS) pharyngitis is still controversial. Subjects were 226 children with a history of at least one episode of GABHS pharyngitis. Recurrence within the follow-up period (3 weeks after initiation of therapy) occurred in 7 of the 77 children in the 5-day treatment group and in 1 of the 149 children in the 10-day treatment group; the incidence of recurrence being significantly higher in the 5-day treatment group. Bacteriologic treatment failure (GABHS isolation without overt pharyngitis) at follow-up culture was observed in 7 of the 77 children in the 5-day treatment group and 17 of the 149 children in the 10-day treatment group. There was no statistical difference between the two groups. A 5-day course of oral cephalosporins is not always recommended for treatment of GABHS pharyngitis in children who have repeated episodes of pharyngitis.